Plant Leaf Disease Image Retrieval Using Color Moments - Jayamala Kumar Patil; Raj Kumar (Institute of Advanced Engineering and Science, 2013)
This paper presents a Content Based Image Retrieval (CBIR)method for plant leaf image retrieval, intended for identification of leaf diseases. We used color features to extract the contents of leaf images. The color features are extracted using first three color moments. For similarity measurement median value of moment feature vectors is used. The method is studied for three different color spaces i.e. RGB, HSV & YCbCr. The experimental result shows that HSV color space provides better results for plant leaf disease retrieval.DOI: http://dx.doi.org/10.11591/ij-ai.v2i1.1319